Differences in Clinical Characteristics of Patients with Valvular and Non-Valvular Atrial Fibrillation - Istirohatul Ahadiyah; Pipin Ardhianto; Firdaus Wahyudi; Mochamad Ali Sobirin (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Background: There is an increasing global prevalence of atrial fibrillation (AF), including in Indonesia. Based on the presence of mitral stenosis and/or prosthetic valve, AF is divided into two groups, namely valvular AF and non-valvular AF. The differences in clinical characteristics between valvular and non-valvular AF in Indonesia, especially in Semarang, have not been described. This study aimed to determine the differences in clinical characteristics between valvular and non-valvular AF in Semarang. Methods: This study was an observational analytic study with a cross-sectional design and was performed in July-August 2020. The subjects were 54 AF patients, which were divided into two categories, namely valvular (n=28) and non-valvular (n=26) AF. The data were collected from medical records. The differences between the two groups were analyzed with bivariate analysis. Results: The patients with valvular AF were predominantly female (82.1% vs 69.2%; p <0.001), of a younger age (46.54 ± 12.20 vs 61.04 ± 8.68; p <0.001), more likely to have rheumatic heart disease (46.4% vs 3.8%; p <0.001), and have had heart surgery (57.1% vs 0%; p <0.001). The patients with non-valvular AF were more likely to have hypertension (17.9% vs 80.8%; p <0.001), myocardial infarction (0% vs 19.2%; p = 0.021), dyslipidemia (7.1% vs. 42.3%; p = 0.003), and higher BMI (21.03 ± 4.16 vs 25.48 ± 4.20; p <0.001). The INR values in most of the AF patients have not reached the target. The valvular AF patients were more likely to be taking warfarin (100% vs 80,8%, p=0,021) and diuretic therapy (96,4% vs 57,7%, p=0,001). Conclusion: There are significant demographic and clinical characteristics differences between valvular and non-valvular AF.